DEVELOPMENT OF A STAKEHOLDER-ORIENTED POLICY COMMUNICATION STRATEGY FOR EFFECTIVE POLICY DISSEMINATION: A CASE STUDY OF PT BANK SUMUT, MEDAN BRANCH - Pangeran; Muhammad Thariq (Academic Solution Publisher, 2026)
This study examines policy communication at PT Bank SUMUT Medan Branch, focusing on its influence on policy dissemination effectiveness and the development of a stakeholder-oriented strategy. Using a sequential explanatory mixed methods design, quantitative data were collected from 250 employees and relevant stakeholders through Likert-scale questionnaires, while qualitative data were obtained through interviews and FGDs. SEM-PLS results show that policy communication significantly affects policy dissemination effectiveness (β = 0.149; p = 0.001) and stakeholder orientation (β = 0.306; p < 0.001). Stakeholder orientation has the strongest effect on dissemination effectiveness (β = 0.732; p < 0.001) and significantly mediates this relationship (β = 0.224; p < 0.001). The model explains 62.5% of policy dissemination effectiveness. Qualitative findings identify communication barriers as contextual challenges. The study proposes the PRINCEPS Model, integrating clear messaging, digital platforms, stakeholder engagement, SOPs, and HR competency development for sustainable policy dissemination in regional banking organizations effectively.